2007
DOI: 10.1111/j.1542-4758.2007.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of blood volume changes during ultrafiltration pulses and natriuretic peptides in the assessment of dry weight in hemodialysis patients

Abstract: Changes in blood volume (BV) during dialysis as well as plasma levels of brain natriuretic peptide (BNP) and N-terminal (NT) pro-BNP levels are possible tools to assess dry weight in hemodialysis (HD) patients. The aim of the study was to compare these parameters with other non-invasive techniques used to assess dry weight in HD patients, and to study their relation with intradialytic hypotension (IDH) and the presence of cardiovascular disease BV changes during HD, both during regular dialysis and during an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
0
25
1
Order By: Relevance
“…BNP data have been rarely analyzed with BVM. Both van de Pol et al [19] and De Mauri et al [20] reported that a higher refilling rate with a flatter BVM slope was associated with higher BNP level, reflecting fluid overload. No comparison exists between these tools in managing fluid in chronic HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…BNP data have been rarely analyzed with BVM. Both van de Pol et al [19] and De Mauri et al [20] reported that a higher refilling rate with a flatter BVM slope was associated with higher BNP level, reflecting fluid overload. No comparison exists between these tools in managing fluid in chronic HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, in many patients with left ventricular dysfunction, parameters indicating ventricular diastolic dysfunction were increased, rising to 86% in the series reported by Kalfallah et al [12], and clinical symptoms of ventricular failure were often absent. In these dialysis outpatients, echocardiography was a very useful marker to assess volume overload [13,14] using the diameter of the inferior vena cava. Because it is difficult to obtain the diameter of the inferior vena cava in these patients, and in accord with other authors [15], we think that LA diameter and volume may improve the morphophysiologic expression of volume overload and may reduce the probability of assessment errors.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies have generally favored methods based on bioimpedance measurements, which provide an assessment of extracellular and intracellular volume and total body water. [2][3][4] A variant of this technique in which continuous intradialytic measurements are confined to the calf shows particular promise because the relative volume of excess extracellular fluid is greatest in the lower extremities. 5 During dialysis, plasma refilling is more dynamic from the leg in comparison with the trunk or arms, suggesting that the calf could be used as a window to monitor intradialytic changes in whole-body extracellular fluid volume.…”
mentioning
confidence: 99%